Enhanced glucosamine production from Aspergillus oryzae NCH-42 via acidic stress under submerged fermentation. Issue 1 (1st January 2021) - Li, Jia-Shiun; Chew, Yin-Ming; Lin, Meng-Chi; Lau, Yie-Qie; Chen, Chin-Shuh
ABSTRACT: Glucosamine (GlcN) has been widely used to treat osteoarthritis. However, GlcN derived from crustacean shells has several drawbacks, and it is not vegan-friendly. Here, we produced GlcN from the biomass of Aspergillus oryzae NCH-42 and investigated the effects of environmental factors (e.g. carbon and nitrogen sources, temperature, and pH) on the GlcN production of the fungal biomass. The acidic stress resulted in significantly higher GlcN content in the cell wall of A. oryzae NCH-42. Moreover, the SEM examination revealed that the mycelial structure grown at pH 2.5 was thick and sturdy, compared to that at neutral pH conditions. The final yield of GlcN could be enhanced by up to 7.75-fold by cultivating at modified PDB with an initial pH of 2.5 at 30°C for 4 days. In this study, the GlcN content of A. oryzae biomass could reach up to 0.31 g/g biomass, indicating its high potentiality for GlcN production.